Bioethics : methods, theories, domains - Düwell, Marcus, 1962- (Biomedical law and ethics library, 2013)
"This book is a philosophically-oriented introduction to bioethics. It offers the reader an overview of key debates in bioethics relevant to various areas including; organ retrieval, stem cell research, justice in healthcare and issues in environmental ethics, including issues surrounding food and agriculture. The book also seeks to go beyond simply describing the issues in order to provide the reader with the methodological and theoretical tools for a more comprehensive understanding of current bioethical debates. The aim of the book is to present bioethics as an interdisciplinary field, to explore its close relation to other disciplines (such as law, life sciences, theology and philosophy), and to discuss the conditions under which bioethics can serve as an academically legitimate discipline that is at the same time relevant to society. As a systematic and methodologically rigorous overview, Bioethics: Methods, Theories, Domains will be of particular interest to academics and students in the disciplines of Law, Medicine, Ethics and Philosophy"--